Assessing the causal relationship of remote work and employee productivity–a study of corporate Malaysia - Seng, Barry Wang Lim; Ainin, Sulaiman; Zakaria, Nadisah; Foo, Siong Min (Cogent OA, 2025)
The rise of remote work (RW), accelerated by the global pandemic, has reshaped work dynamics, driven by technological advancements and a focus on work-life balance. The main aim of this article to study impact on RW on employees’ productivity. Empirical data was collected via a survey questionnaire on public sector employees. A total of 105 responses were analysed using PLS-SEM. Specifically, the study analyses the role of organisational support, technology availability (i.e. access to required devices and digital infrastructure for effective job execution) and employee wellbeing towards employee’s productivity. The study also analysed the role of socioeconomic (such as nationality, gender, age, marital status and household income levels) as a moderator between these variables. In addition, the study analysed whether worker preference mediates the relationship between RW and employee productivity. Results showed technology’s availability significant positive influence, while organisational support had a positive but insignificant impact. Employee well-being is strongly correlated with productivity. Socioeconomic profiles had no clear impact, but self-preference (SP) mediated effects. The findings imply that RW can increase employees’ productivity but organisations must be willing to invest in technology (to ensure it is readily available and accessible, foster supportive environments and align practices with individual preferences.